Recent Advances in Antiviral Activities of Triterpenoids - Yue Liu; Liangyu Yang; Hong Wang; Yongai Xiong (MDPI AG, 2022)
Triterpenoids, important secondary plant metabolites made up of six isoprene units, are found widely in higher plants and are studied for their structural variety and wide range of bioactivities, including antiviral, antioxidant, anticancer, and anti-inflammatory properties. Numerous studies have demonstrated that different triterpenoids have the potential to behave as potential antiviral agents. The antiviral activities of triterpenoids and their derivatives are summarized in this review, with examples of oleanane, ursane, lupane, dammarane, lanostane, and cycloartane triterpenoids. We concentrated on the tetracyclic and pentacyclic triterpenoids in particular. Furthermore, the particular viral types and possible methods, such as anti-human immunodeficiency virus (HIV), anti-influenza virus, and anti-hepatitis virus, are presented in this article. This review gives an overview and a discussion of triterpenoids as potential antiviral agents.